Development and in vitro/in vivo evaluation of thermo-sensitive in situ gelling systems for ocular allergy - Umay Merve Güven; Murat Sami Berkman; Behiye Şenel; Yasemin Yazan
Ocular allergy is one of the most common disorders of the eye surface. Following diagnosis this condition is typically treated with preparations containing antihistamines. However, anatomy of the eye and its natural protective mechanisms create challenges for ocular drug delivery. Rapid elimination of antihistamine substances due to short residency times following application can lead to insufficient treatment of ocular allergies. With this in mind, the aim of this study was to prepare a controlled ocular delivery system to extend the retention time of olopatadine hydrochloride (OLO) and in doing so to reduce the need for frequent application. We developed extended-release ocular in situ gelling systems for which in vivo retention times were determined in sheep following in vitro characterization and cytotoxicity studies. In vivo results were then compared to commercially available Patanol eye drops. the transparent gels formulated using appropriate amounts of polymers and having longer ocular retention times appear to be a viable alternative to commercially available eye drops.